Pengaruh latihan boteli dan modifikasi frekuensi dalam meningkatkan keterampilan groundstroke forehand dalam tenis - Agustiyanto, Agustiyanto (Universitas Nusantara PGRI Kediri, 2023)
Learning to improve sports skills takes a long time to master. Assistive devices and modifications to training time are needed to improve students' abilities. This study aims to determine the effectiveness of use by modifying exercises that can help in mastering forehand groundstroke skills in sports students learning court tennis. The subjects of the study were 48 sports students, with male gender. The method of dividing subjects into treatment groups is to match pairs in consideration of Pretest scores before treatment. This research instrument uses Kemp-Vincent Rally Test with validity levels of 0.80 and 0.93 while reliability is 0.90 and 0.86. The data analysis technique uses a paired t-test with a signification level of α = 0.05. Test the normality and homogeneity of groundstroke skills using the Bartlet test. The analysis of these results showed that boteli exercises with a weekly frequency of twice affected forehand groundstroke skills. Second-time comparison of sig data results. (2-tailed), values 0.000 < 0.05. This means h0 rejected h1 is acceptable, so it can be concluded that the frequency of exercise a week is twice as good as the frequency of exercise once a week in influencing boteli exercise to improve the reliability of tennis groundstroke forehand rally. This study concludes that providing equipment modifications and training time can improve the ability of sports students to master rally forehand groundstroke skills.